Prevalence of HIV Antiretroviral Drug Resistance and Its Impacts on HIV-1 Virological Failures in Jiangsu, China: A Cross-Sectional Study. (11th October 2016) - Zhou, Ying; Lu, Jing; Wang, Jinge; Yan, Hongjing; Li, Jianjun; Xu, Xiaoqin; Zhang, Zhi; Qiu, Tao; Ding, Ping; Fu, Gengfeng; Huan, Xiping; Hu, Haiyang
Abstract : Antiretroviral therapy (ART) has been shown to improve survival of patients with Human Immunodeficiency Virus (HIV) infection and to reduce HIV-1 transmission. Therefore, the Chinese central government initiated a national program to provide ART free of charge to HIV-1 patients. We conducted a cross-sectional survey in Jiangsu province to determine the level of drug resistance (DR) in HIV-1 infected patients and the correlates of DR in virological failures in 2012. Approximately 10.4% of the HIV-1 patients in the study experienced virological failure after one year of ART and were divided into drug sensitive and drug resistant groups based on genotype determination. The viral loads (VLs) in the drug resistant group were significantly lower than the drug sensitive group. There were two independent predictors of virological failure: male gender and increasing duration of treatment. The primary mutations observed in the study were against nucleoside reverse transcriptase inhibitors (NRTIs) which were M184V (79.45%) and K103N (33.70%) in nonnucleoside reverse transcriptase inhibitors (NNRTIs). The overall rate of DR in Jiangsu province is still relatively low among treated patients. However, close monitoring of drug resistance in male patients in the early stages of treatment is vital to maintaining and increasing the benefits of HIV ART achieved to date.